Large-scale planetesimal formation by streaming instability. Issue Volume 8:Issue S299(2013) (6th January 2014) - Yang, Chao-Chin; Johansen, Anders
Abstract: In current theory of planet formation, streaming instability is one of the most promising mechanisms to overcome the meter-barrier in the course of core accretion. Almost all previous works, however, were focused on a local region of protoplanetary disks with a limited size of about 0.2 gas scale heights. Only one radial filamentary particle concentration was seen in these studies. To address this, we conduct the largest-scale simulations of this kind to date, up to 0.8 gas scale heights both horizontally and vertically. We demonstrate that streaming instability remains robust on large scale and multiple radial particle concentrations exist in large enough boxes. This result may be important in characterising the feeding zone of planetesimal formation.